Implementation Considerations for Fast Payment Systems - World Bank (World Bank, Washington, DC, 2021)
The World Bank (WB) has been monitoring closely the developments of fast payment systems (FPS) by central banks and private players across the globe. This comprehensive study of FPS implementations across the world has resulted in the design of a policy toolkit on the implementation of FPS, in order to guide countries and regions on the likely alternatives and models that can assist them in their policy and implementation choices when they embark on their respective FPS journeys. Different objectives, policy and or business, are often articulated as driving the decision behind FPS implementation. Some of those include achieving general efficiencies, having new functionalities, allowing broader access, improving security, and achieving interoperability.